Influence of stance position on stress and performance factors during snowboarding - Connor, D. A. (2013)
This research project is the first of its kind examining stress and performance factors in snowboarders. Snowboarding is a highly competitive and popular sport with events including racing in the winter Olympics, half pipe and big-air events in the X-Games, and millions of recreational riders worldwide. While most research regarding the sport has focused on injury type and rate, as well as mechanical factors at the ankle joint, there is a lack of research with respect to the basic stress response during participation. Finishing time increased significantly during SS riding, consistent with expectations, while the increase in RPE was practically significant, but not statistically different. Also consistent with the hypotheses, maximum degrees of board tilt decreased significantly during SS riding. The results of this experiment may have implications for instruction of novice snowboarders. When riding in the SS, there is a very marked increase in time to complete a snowboarding task, decreased board tilt angles indicative of lesser skill, and increased RPE. Given these results are obtained from advanced level riders, it is plausible that a similar, or greater change in these factors may occur in novice or beginning level riders riding switch. Furthermore, similarity in the heart rate and blood lactate response in both domains seem to indicate that a similar absolute intensity is achieved in both stance positions. One possible explanation for these results is that the general stress associated with riding in either domain is due to different mechanisms. In a rider's PS the intensity and resultant stress may be due to increased angulation of the body due to increased board tilt and faster speed of travel. In the switch stance the intensity may be due to stress associated with performing in an abnormal fashion, and increased isometric stabilization and tension. Due to the these results, and the concept of bilateral transfer when learning a physical skill, it seems appropriate to recommend instruction that equally and immediately focuses on PS and SS riding in order for snowboarders to learn the skill more quickly than learning in one domain and then the other. Given that most injuries occur in beginners, if snowboarders are instructed equally in both domains and experience less stress when riding due to increased skill level, it is possible that injury rates may be reduced. During snowboarding events and styles such as big air, half-pipe, and park riding including free style riding, snowboarders often land in their switch stance. For individuals participating in these types of riding, and others learning the skill, practicing and learning snowboarding in both domains is a practical strategy for skill development and improved performance in both stance positions.